An investigation of an adaptive neuro-fuzzy inference system to predict the relationship among energy intensity, globalization, and financial development in major ASEAN economies - Iqbal Hussain, Hafezali; Slusarczyk, Beata; Kamarudin, Fakarudin; Mohd Thas Thaker, Hassanudin; Szczepańska-Woszczyna, Katarzyna (MDPI, 2020)
The enhancement of the financial sector significantly drives a nation’s economy and thereby increase energy intensity. Considering this situation, the current study aims to examine the link between globalization and financial advancements with the energy intensity of the top 5 ASEAN (Association of Southeast Asian Nations) economies. The development structure of the ASEAN region is considered significant for having stable growth. The authors used the annual data from 1990 to 2018 for five of the largest ASEAN economies: Singapore, Malaysia, Thailand, Indonesia, and the Philippines. The present study used novel methodology, the Adaptive Neuro-Fuzzy Inference System (ANFIS), to examine the nonlinear behaviour among globalization, financial development, and energy intensity in the top 5 ASEAN countries. The study results using ANFIS confirm that globalization and financial development are positively correlated and have a significant impact on the energy intensity level in the top ASEAN countries. The results further suggest that globalization and financial development increase the level of energy intensity more in the countries that are developed relative to their peers in the top ASEAN countries. Moreover, the outcomes of ANFIS also suggest that those countries, which are more globalized and financially developed, have more potential to increase the level of energy intensity. Therefore, the government needs to focus more on projects that involve renewable energy and are environmentally friendly.